1982
DOI: 10.1016/0014-5793(82)81316-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of estrogen on the concentration of ovalbumin gene sequence in the 2 M NaCl residual fraction of oviduct chromatin

Abstract: Oviduct chromatin was isolated from both estrogenized and non-estrogenized hens. Extraction of the chromatin with 2 M NaCl removed a majority of the proteins, and the resulting DNA was then separated into two components: (1) a major fraction which was virtually protein-free; and (2) a minor fraction which was complexed with proteins. It was found that the DNA fraction that is complexed with proteins contained ovalbumin gene sequences and that the concentration of these sequences could be boosted by estrogen-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1984
1984
1988
1988

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Our previous observations that active tissue-specific genes (18)(19)(20) are concentrated in the DNA-P fraction along with RNA (19) also suggest that the preferential precipitation of these active genes could be due to the fact that these genes contain high concentrations of nascent RNA complexed with RNA polymerase (29). However, in the case of erythrocytes in which transcription of the f3-globin gene is not occurring (23), the observation that this gene is concentrated in the nuclear matrix DNA to about the same extent as in reticulocyte DNA-P (18) Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous observations that active tissue-specific genes (18)(19)(20) are concentrated in the DNA-P fraction along with RNA (19) also suggest that the preferential precipitation of these active genes could be due to the fact that these genes contain high concentrations of nascent RNA complexed with RNA polymerase (29). However, in the case of erythrocytes in which transcription of the f3-globin gene is not occurring (23), the observation that this gene is concentrated in the nuclear matrix DNA to about the same extent as in reticulocyte DNA-P (18) Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is also known that RNA polymerase-DNA complexes are not dissociated by high salt concentration, and therefore factors for transcription and subunits of RNA polymerase associated with DNA may become matrix components (28). Our previous studies on chromatin isolated from tissues active in ,3-globin (18), human placental lactogen (19), and ovalbumin (20) gene expression suggested that the 2 M NaCl-insoluble DNA-protein fraction contained high concentrations of their respective specialized gene sequences. Therefore, nonrandom sequences of DNA are found both in nuclear matrix DNA and in DNA-P. Robinson et al (21) suggested that the observed preferential association of the ovalbumin gene with nuclear matrix DNA isolated from chicken oviduct may have some implication for gene expression and the organization of nuclear DNA into supercoiled loop domains.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, proteins in the CP-3 fraction appear to contain "acceptor activity" which endow DNA with the capacity for nativelike binding of PR. Similar fractions of tightly bound, non-histone proteins are associated with the nuclear matrix (Berezney & Coffey, 1977; Barrack & Coffey, 1980), with active-diffuse chromatin fractions (Wang et al, 1976) and with active structural genes (Bekhor & Mirell, 1979;Gates & Bekhor, 1980; Norman & Bekhor, 1981; Mirell & Bekhor, 1982). This same class of proteins has been reported to enhance transcription of DNA by increasing the binding of RNA polymerase to DNA (Bekhor & Samal, 1977).…”
mentioning
confidence: 83%